The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fpls.2018.00906
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Functional Analysis of NADPH Oxidase Family Genes in Wheat During Development and Environmental Stress Responses

Abstract: As the key producers of reactive oxygen species (ROS), NADPH oxidases (NOXs), also known as respiratory burst oxidase homologs (RBOHs), play crucial roles in various biological processes in plants with considerable evolutionary selection and functional diversity in the entire terrestrial plant kingdom. However, only limited resources are available on the phylogenesis and functions of this gene family in wheat. Here, a total of 46 NOX family genes were identified in the wheat genome, and these NOXs could be cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 79 publications
4
39
1
Order By: Relevance
“…These suggest that the Gossypium Rbohs are originated from a common ancester. The number of exons for Gossypium Rbohs was 10-15, similar to that in Rbohs in Arabidopsis, rice, maize, wheat, canola and soybean (Chang et al, 2016;Hu et al, 2018;Li et al, 2019a;Li et al, 2019b;Liu et al, 2019;Navathe et al, 2019). Additionally, the majority of the Gossypium Rbohs had the conserved EF hand domains, and NADPH_Ox, Ferric_reduct, FAD_binding_8 and NAD_binding_6 motifs of higher plants (Fig.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…These suggest that the Gossypium Rbohs are originated from a common ancester. The number of exons for Gossypium Rbohs was 10-15, similar to that in Rbohs in Arabidopsis, rice, maize, wheat, canola and soybean (Chang et al, 2016;Hu et al, 2018;Li et al, 2019a;Li et al, 2019b;Liu et al, 2019;Navathe et al, 2019). Additionally, the majority of the Gossypium Rbohs had the conserved EF hand domains, and NADPH_Ox, Ferric_reduct, FAD_binding_8 and NAD_binding_6 motifs of higher plants (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…In the present study, we identified 13, 13, 26 and 19 Rbohs in G. arboretum, G. raimondii, G. hirsutum and G. barbadense, respectively ( Table 1). The number of these Rbohs in Gossypium, particularly in G. hirsutum and G. barbadense was larger than that in other plants such as Arabidopsis (10), rice (9), maize (14), Brachypodium distachyon (9), Populus trichocarpa (10), wheat (19), Brassica rapa (14) and soybean (17) (Chang et al, 2016;Hu et al, 2018;Li et al, 2019a;Li et al, 2019b;Liu et al, 2019;Navathe et al, 2019), implying that more sophisticated ROS signal transduction mechanisms may exist in Gossypium. Compared with other crops as mentioned above, Gossypium plants are more tolerant to environmental stresses like drought, high salt, heat stress, and so forth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes are both related with photosynthesis. Hu et al [112] highlighted that NADPH plays a crucial role in biological processes in plants, such as the regulation of the production of reactive oxygen species (ROS) for the stress tolerance [113,114]. Additional GWAS analyses using reduced datasets revealed other interesting genes for this QTL (chromosome 2A, Supplementary Materials Table S8), encoding for the Acyl-CoA N-acyltransferase and the chloroplastic zeaxanthin epoxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Two TaNOX genes have been reported to confer resistance to brown rust infection 40 . To date, 15 TaNOXs have been reported to be co-expressed with different sets of other genes that participate in several critical intracellular processes such as cell wall biosynthesis, defence response, and signal transduction, suggesting vital but diverse roles for these genes in regulating plant growth and stress responses in wheat 43 . Two of these genes (TaNOX8 and TaNOX9) were mapped to chromosome 4DL.…”
Section: Linkage Disequilibrium Analysis and Genome-wide Association mentioning
confidence: 99%